Piracy as threat to Africa’s security and economic development (2018)
The paper explores the links between piracy, security and economic dilemma in Africa. The phenomenal increase in the activities of pirates in the coastal region of Africa in the 1990s brought out more forcefully the need to address the causes and consequences. The paper argues that the significant dependence of African countries on global trade makes maritime transport a crucial factor in Africa’s economic development. However, the scale and sophistication of piracy on the continent threatens the global flows of goods and services across the world’s shipping lines. Thus, the consequences of African piracy manifest themselves locally and globally. The central argument of this paper is that until there is a proper understanding of the geostrategic importance of Africa’s maritime domain, piracy will continue to pose a threat not only to Africa but also to global security and maritime trade. The argument summits that an effective strategy to combat piracy along the coastal region of Africa will require the international community to trace and address the principal cause of the menace